2020
DOI: 10.1002/jcph.1579
|View full text |Cite
|
Sign up to set email alerts
|

Protective Association Between Calcium Channel Blocker Use and Breast Cancer Recurrence in Postsurgical Women: A Population‐Based Case‐Control Study in Taiwan

Abstract: Neoadjuvant chemotherapy induces metastasis of residual breast cancers through activation of tumor-associated macrophages. Previous studies have indicated that calcium channel blockers (CCBs) exert anti-inflammatory and antimigratory effects on macrophages via attenuating Ca 2+ entry into macrophages. However, no existing empirical research has addressed the relationship between previous CCB use and breast cancer recurrence. In this study, 4840 Taiwanese women aged ࣙ20 years with breast cancer who underwent br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A few studies showed that CCBs were associated with a better survival for various cancers, including GC 23,43,44 . However, to our knowledge, this is the first report on the potential chemopreventive effect of CCBs on GC using a well‐defined cohort of H pylori ‐eradicated subjects.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A few studies showed that CCBs were associated with a better survival for various cancers, including GC 23,43,44 . However, to our knowledge, this is the first report on the potential chemopreventive effect of CCBs on GC using a well‐defined cohort of H pylori ‐eradicated subjects.…”
Section: Discussionmentioning
confidence: 81%
“…42 A few studies showed that CCBs were associated with a better survival for various cancers, including GC. 23,43,44 However, to our knowledge, this is the first report on the potential chemopreventive effect of CCBs on GC using a well-defined cohort of H pylorieradicated subjects. Apart from the heterogeneity in definition of drug exposure, comparators and study design, all prior studies failed to adjust for important confounding factors that affect the causal interpretation.…”
Section: Discussionmentioning
confidence: 85%
“…Certainly, Li et al demonstrated repeatedly that in patients treated for hypertension or other cardiovascular diseases, with calcium channel blockers (CCB), this would increase the risk, by up to two times, of developing breast cancer but also following a dose long term, which is supported by other studies [ 13 , 14 , 15 ]. Conversely, more recent studies do not suggest any increased risk of developing breast cancer with long-term or punctual CCB intake, nor is it associated with greater mortality [ 16 , 17 ] and would protect against a risk of recurrence in women aged 20 to 54 [ 18 ]. Nevertheless, the use of CCB in breast cancer patients could be associated with the development of lymphedema as well as immunosuppressive effects within the tumor microenvironment [ 19 , 20 ], thus justifying the importance of calcium in breast cancer.…”
Section: Introductionmentioning
confidence: 99%